Isolation of highly copper-resistant bacteria from deep-sea hydrothermal fields and description of a novel species Marinobacter metalliresistant sp. nov - Yu, Tong; Qin, Meng; Shao, Zongze; Zhao, Yuemei; Zeng, Xiang (Frontiers in Microbiology, 2024)
Hydrothermal vents are rich in heavy metals. Twelve highly copper-resistant bacteria (up to 6-10 mM) were isolated from deep sea hydrothermal fields. They were affiliated with the Pseudoalteromonas (4), Marinobacter (3), Halomonas (2), Psychrobacter (1), and Pseudomonas (1) genus in the γ-Proteobacteria, and the Sphingomonas (1) genus in the α-Proteobacteria. The presence of copper in the medium obviously induced the amount of polysaccharides and proteins in the crude extracellular polymeric substances (EPS) produced by Halomonas sp. CuT 3-1, Pseudoalteromonas sp. CuT 4-3 and Marinobacter metalliresistant CuT 6, which could absorb 40 to 50 mg•g-1 copper. By physiologic and genomic analysis, it revealed that the copper resistance capability exhibited by these strains in hydrothermal fields is likely attributed to the production of exopolymeric substances, such as polysaccharides and proteins, as well as active transport or efflux mechanisms for heavy metals. We further described a novel species, Marinobacter metalliresistant sp. nov. CuT 6T, which exhibited a higher copper resistance and encoded more heavy metal resistance-related genes than other Marinobacter species.